Modification of Carbon Paste Electrode with Imprinted Zeolite A as a Sensor for Potentiometric and Voltammetric Amitriptyline Analysis - Miratul Khasanah; Alfa Akustia Widati; Tias Fadillah; Naftalia Wirdatul Ummah; Evrillia Puspitasari; Vina Aminatuz Zuhriyyah; Titah Aldila Budiastanti (Pakistan Journal of Analytical & Environmental Chemistry)
Imprinted zeolite (IZ) has been used as a material to modify carbon paste electrodes and applied the modified electrode as a potentiometric and voltammetric sensor for amitriptyline (AMT). IZ was made from zeolite A, which is synthesized with an AMT/Si mole ratio of 0.03, then AMT was extracted from the zeolite framework to leave the active site that will recognize the AMT molecule selectively. Modified electrodes prepared with a mass ratio of paraffin, activated carbon, and IZ of 4:5:1 showed optimum performance as sensors in potentiometric analysis, which is expressed by a Nernst factor of 60.8 mV/decade, a detection limit of 9.85×10-7 M, accuracy of 88-107%, recovery of 88.6% (n = 2), a response time of 60-89 s, and a life time longer than 18 weeks with more than 135 times of use. The presence of glucose, sucrose, and lactose did not interfere in AMT analysis. Measurement of the AMT using the modified electrode by voltammetry resulted in linearity of the calibration curve (R) of 0.9904, detection limit of 4.2×10-8 M, precision of 82.9-97.7%, sensitivity of 552 nA/M, and recovery of 103.1% (n = 3). The modified electrode showed 2-4 times more selectiveness to AMT than the bare carbon paste electrode in the glucose matrix. Based on its advantages, the modified electrode is recommended for use in the pharmaceutical field to monitor AMT concentration in affordable antidepressant medicine, namely Amitriptyline Hydrochloride.